Using technology to support effective instruction in early childhood settings - Greg Conderman; Myoungwhon Jung (Problemy Wczesnej Edukacji)
Technology is increasingly becoming a popular and effective instructional tool used by early childhood educators. because of its popularity and potential to increase student learning, this article provides guidelines for early educators regarding the wise and intentional use of technology and offers specific examples of both educational and assistive technologies.